Effect of heat treatment on the nutritional value of low-inhibitor soybeans for nursery growing, and finishing pigs - A J Lewis; M A Giesemann; Jim L Nelssen; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1989)
Two hundred forty nursery pigs (12.8 lb initial wt) were used in a 28-d growth assay to determine the nutritional value of Williams 82 soybeans with (+K) and without (-K) gene expression for the Kunitz trypsin inhibitor. Treatments were soybean type (+K and -K) and heat treatment (none, half-roasting, and full-roasting time), in a factorial arrangement. The soybeans were heated in a Roast-a-Tron roaster, ground, and added to corn-dried whey diets formulated to be limiting in lysine (.88%). Pigs fed diets with -K soybeans gained 21% faster and were 13% more efficient than pigs fed diets with + K soybeans. As heat treatment was increased to full-roasting, rate and efficiency of gain increased. The + K soybeans were of lower nutritional value than the - K soybeans when fed raw or half-roasted, but the two soybean types were of similar nutritional value when fully roasted. Two additional experiments (66 individually fed pigs each) were conducted using growing and finishing pigs. The soybeans were added to corn-based diets formulated to contain .60 and .48% lysine for the growing and finishing phases, respectively. Growing pigs fed diets with the - K soybeans gained 10% faster, were 10% more efficient, and had 13% lower fat depth at the last rib than pigs fed the + K soybeans. Finishing pigs fed diets with the - K soybeans were more efficient and had lower fat depths than pigs fed the +K soybeans. Considering all three growth phases, the low-inhibitor (-K) soybeans were of greater nutritional value than the conventional (+ K) soybeans, with the greatest difference observed when the soybeans were fed raw. The nutritional value of both soybean types (+K and - K) was optimized with full-roasting. The half-roasting treatment was not sufficient to optimize the nutritional value of the low-inhibitor soybeans.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Low-inhibitor soybeans; Kunitz Trypsin inhibitor; Raw soybeans; Roasting; Pig